Fighting Zero Hunger Amidst The Pandemic - Froilan Mobo; Ana Liza Garcia (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2022)
One of the goals of the International Human Rights Movement Philippines is to help the Pastoral Care for Children at St. Anthony of Padua Parish, Subic, Zambales, Philippines in sustaining and fighting zero hunger because the majority of the residents of Matain, Subic, Zambales was greatly affected by the global pandemic, some of them lost their jobs and others lost their business income. The Project was conducted last February 27, 2022 in celebration of the Birthday of the Founding Chairman of IHRM, Dr. Rana Basharat, and the Ambassador at Large / Country Director of the IHRM Philippines in sponsoring the Feeding Program in support to the United Nations SDG 2 Zero Hunger, the said event was also participated by the Honorable Mayor Jonathan John Khonghun, Mayor of Subic, Zambales, Philippines The Researchers would like to cite that there is a need to address the issues on malnourishment and hunger in collaboration with the Government in attaining the Sustainability and Development.